1984
DOI: 10.1007/bf02270838
|View full text |Cite
|
Sign up to set email alerts
|

Suspended spicules associated with the enhanced bright network in an active region

Abstract: Abstract. The progressive rotation from the limb onto the disk of a long-lived cluster ofcoaligned He spicules was observed at high spatial resolution on the fringe of a large complex of activity. Although individual spicules were steadily changing, the organized cluster appeared consistently suspended above the photospheric limb when viewed in the wings of He ([A2[ ~ 0.9 ~). The phenomenon is the counterpart near an active region of the dark band discovered in the quiet low chromosphere by Loughhead (1969). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…• Gap at spicule bases. The sometimes-observed gap between the photospheric limb and the bottoms of spicules (e.g., Gaizauskas 1984) could result from the spire of the spicule forming by reconnection at the height of the neighboring bipole (Fig. 1).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…• Gap at spicule bases. The sometimes-observed gap between the photospheric limb and the bottoms of spicules (e.g., Gaizauskas 1984) could result from the spire of the spicule forming by reconnection at the height of the neighboring bipole (Fig. 1).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Nevertheless, there are discrete bright patches that can reach up to 40% above the quiet Sun brightness temperature, especially near the polar limb. It is known that there are no spicules over chromospheric plages (Shibata & Suematsu 1982;Zirin 1988) and the same behavior was observed for faculae (Gaizauskas 1984). Moreover, polar faculae and polar limb brightening are both anti-correlated with the sunspot cycle (Efanov et al 1980;Makarov & Makarova 1996;Koshiishi 1996;Selhorst et al 2003).…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, we suggest that the discrete bright polar patches observed in 17 GHz maps are due to holes in the spicule forest right above polar faculae. Gaizauskas (1984) observed that there are no spicules over faculae as well as over plages (Zirin 1988). Moreover, faculae are known to be more abundant near the poles (Erofeev 2001;Unruh et al 1999;Ortiz et al 2002) and the radio polar bright regions are close to the polar faculae regions (Riehokainen et al 1998;Gelfreikh et al 2002).…”
Section: Model With Spicule-less Regionsmentioning
confidence: 97%